2017
DOI: 10.12669/pjms.334.12647
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of extended-spectrum-beta‑lactamase producing E. coli from healthy individuals, patients, sewage sludge, cattle, chickens and raw meat

Abstract: Objective:The present study aimed to determine the frequency and antimicrobial profile of ESBL-producing isolates of E. coli in different environments.Methods:This cross-sectional study was conducted at The Children’s Hospital and The Institute of Child Health, Lahore from July to December 2015. The faecal specimens from healthy individuals, patients, sewage sludge, cattle, chickens and raw meat (n = 122) were processed for microbiological analysis using MacConkey agar supplemented with cefotaxime. The identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(23 reference statements)
2
8
3
Order By: Relevance
“…Thus, comparison of our results from different countries is may not be feasible due to differences in the study methodology, such as method of enrichment and isolation procedures, differences in sample size and type of sample and how and when it was collected. However, the proportion of ESBL- producing E. coli strains obtained in this study was lower than the study finding in Vietnam [14] and Pakistan [15] and higher than the study finding in China [16]. In addition to the above methodological differences, the observed differences might be also related with the frequent and miss-use practices of third generation cephalosporins in humans and food animal, since the use of these antibiotics greatly linked to the recent emergence of ESBLs-producing bacteria.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Thus, comparison of our results from different countries is may not be feasible due to differences in the study methodology, such as method of enrichment and isolation procedures, differences in sample size and type of sample and how and when it was collected. However, the proportion of ESBL- producing E. coli strains obtained in this study was lower than the study finding in Vietnam [14] and Pakistan [15] and higher than the study finding in China [16]. In addition to the above methodological differences, the observed differences might be also related with the frequent and miss-use practices of third generation cephalosporins in humans and food animal, since the use of these antibiotics greatly linked to the recent emergence of ESBLs-producing bacteria.…”
Section: Discussioncontrasting
confidence: 90%
“…In this study 26 (74.3%) of E. coli isolates were showed co-resistance to three or more classes of antibiotics, such as tetracycline, co-trimoxazole and erythromycin plus β- lactam group of antibiotics. The higher rate of multi-drug resistant (MDR) isolates were also reported in other area of Ethiopia [32], Vietnam [14] and Pakistan [15], in which (56.5 to 96.3%) of ESBLs-producing and non- ESBLs-producing E. coli isolates were showed multiple drug resistance for three or more antibiotics. The result of this study, combined with data from previous studies in different countries, suggests that unhygienic practice of food handling and processing is major contributors to the dissemination of not only ESBL- E. coli but also MDR bacteria.…”
Section: Discussionmentioning
confidence: 72%
“…This is similar to the findings from Luvsansharav U et al in Japon (69.3%) in 2012 on Prevalence of and risk factors associated with fecal carriage of CTX-M blactamase-producing Enterobacteriacae in rural Thai communities [29]. A high prevalence above 50% has also been observed among healthy individuals (57%) for Escherichia coli in a study conducted by Saleem et al in 2017 in Pakistan [30]. On the other hand, studies conducted by Michaud et al in Senegal in 2014 among farm workers showed a low digestive carrying rate (9.4%) [18].…”
Section: Discussionsupporting
confidence: 89%
“…Studies have shown that extended-spectrum β-lactamases (ESBL)—producing E . coli are resistant to several antibiotics especially penicillins and cephalosporins however, they are susceptible to cephamycins and carbapenems [28]. In our study, resistance rates to the third and fourth generation cephalosporins were quite low and observed only among poultry-sellers at live bird markets.…”
Section: Resultsmentioning
confidence: 54%